Perlindungan Hukum Bagi Pekerja Digital Studi Perbandingan Pengakuan Status Kerja Driver Ojek Online Di Indonesia Dan Prancis - Hatmadja, Gigih Tri (STAIN MAJENE, 2025)
Digital transformation has generated the gig economy, reshaping employment relations, particularly for online motorcycle taxi drivers. In Indonesia, drivers are classified as partners, limiting their access to labor protections. In contrast, France has recognized elements of subordination within platform-based work. This study adopts a normative juridical approach combined with comparative legal methodology using functional and law in context perspectives. Analysis follows Eberle’s model, consisting of external law identification, internal law analysis, and functional comparison between legal systems. Indonesia maintains a partnership framework, resulting in drivers not being legally recognized as workers and thus excluded from minimum wages, social security, and protection against unfair termination. Existing regulations fail to address the complexities of digital labor. In France, the 2020 Court of Cassation decision affirmed the presence of subordination between platforms and drivers, granting them the status of workers and access to labor protections. France’s substantive approach ensures social security coverage, collective bargaining rights, and effective dispute resolution mechanisms. Divergent recognition of employment status leads to unequal legal protection effectiveness. Indonesia must adopt a progressive framework that evaluates employment relationships based on factual subordination to ensure fair and comprehensive protection for digital platform workers.